Towards Sustainable Management of Pineapple Residues - Ahmed, Osumanu Haruna (2002)
Studies were conducted to: (i) Investigate the effect of the modification of the existing N, P, and K programme and residue management practice on pineapple fruit yield, (ii) Compare the economic viability of in situ decomposition of pineapple residues untouched (lDPR), i.e. stacking of pineapple residue (leaves, crowns, and peduncles) slashed and raked from 0.60 m x 10 m rows into 0.90 m x 10 m rows (ZBT-zero burn technique), and in situ burning pineapple residues (IBPR) (iii) Quantify the amount of humic acid (HA) that could be extracted from composted pineapple leaves using 0.10M potassium hydroxide (KOH) produced from pineapple leaves and that of analytical grade (0. 10M KOH), (iv) Compare the elemental composition (C, H, N, 0, and S), functional groups (carboxylic, phenolic OH, and total acidity), and spectral characteristics of HA extracted from composted pineapple leaves using KOH from pineapple leaves and that of analytical grade, and (v) Investigate the potential value added agricultural products that could be produced from pineapple leaves.